UJI TARIK BAJA TULANGAN PENGGUNAAN EPOXY CHEMICAL ITEWE NEO SEBAGAI ADHESIF DENGAN VARIASI DIAMETER MENURUT PERATURAN SNI 2847:2019 - Valentana Ardian Tarigan (Universitas Quality, 2023)
Reinforced concrete structures cannot be separated from the use of reinforcing steel as a material that resists the tension that occurs in concrete structures. Specifically for buildings that require steel as reinforcement in new areas where reinforcement has not been installed, a chemical epoxy type of adhesive material is used, which is used in this study, namely Itewe Neo. Steel materials are used to carry out their duties to cover the weaknesses of concrete in terms of tensile loads, and chemical epoxy is used to connect two different materials, namely steel and concrete. The test is carried out to determine the magnitude of the difference in tensile strength of the tested reinforcing material. Experiments on steel with a minimum yield stress of 280 MPa, also known as plain reinforcing steel and reinforcing steel with a minimum yield stress of 420 MPa, also known as fin reinforcing steel. The variation used in this test lies in the diameter of the plain steel bars with diameters of 8, 10 and 12 mm. Fin reinforcing steel with diameters of 10, 13 and 16 mm. The test results show that the deeper the reinforcing steel, the greater the required tensile strength. Other results show that fin steel reinforcement has a greater tensile strength than plain steel reinforcement.